(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background:Primary total knee arthroplasty (TKA) is technically demanding surgery, which if it is done perfectly can give excellent patient satisfaction and pain relief. Still abnormal patellar tracking is the most common complication of primary TKA (24%) and it is the most common cause of revision. Objective :To emphasize on the effectiveness of adherence to certain surgical steps (peroperatively) and to which extent these steps can reduce the incidence of peroperative abnormal patellar tracking in primary TKA. Methods: A prospective descriptive study was conducted in Al-Imamein Al-Kadhimein Medical City from May 2011 to December 2014; it involves 67 patients who underwent unilateral total knee replacement for different pathology and variable knee deformity. Step wise surgical procedure for primary TKA insisting on certain technique and tricks to achieve perfect TKA and finally checking the patellar tracking preoperatively using no thumb test and towel clips test. Results: NEXGENR posterior cruciate substitution design used in 62 patients (92.5%) and condylar constrained knee in 5 patients (7.5%) and abnormal patellar tracking occurred preoperatively only in 1 patient (1.4%). Conclusion: Strict adherence to surgical procedures keeping in mind certain factors, which should be fulfilled is essential for successful peroperative patellar tracking, while postoperative assessment required different investigation like computed tomography or dynamic radiographs to ensure this good patellar tracking and improving the outcome of primary TKA in our country. Keywords: primary TKA, peroperative patellar tracking DOI: 10.22578/IJMS.14.4.2